PENGARUH MEDIA SOSIAL TERHADAP KEPUTUSAN MINAT PEMBELIAN PRODUK ASURANSI SYARIAH PADA GENERASI Z - Humaemah, Ratu; Roy, M. Indrajit; Herdiana, Hikmah (UIN Sultan Maulana Hasanuddin Banten, 2023)
The purpose of this study is to influence social media on the purchase decision of sharia insurance products in generation Z. This study uses quantitative methods with purposive sampling techniques. Respondents in this study are students who belong to generation Z and have used social media. Data collected through questionnaires and evaluations with multiple linear regression show that social media has a significant good and positive influence on the decision of interest in purchasing sharia insurance products in generation Z, while the characteristics of gen Z has such a significant positive influence on decisions intention topurchase sharia insurance goods in generation Z. In the context of marketing sharia insurance products, insurance companies can utilize social media as one of the tools to promote their products to generation Z.